Does financial repression inhibit or facilitate private investment? The case of Ethiopia - Fentaw Leykun Fisseha (Future Business Journal)
Abstract This study examines the impact of financial repression (FR) on private investment in Ethiopia over the period 1980 to 2020. Investigating the consequences of FR policies makes use of the cointegration technique. The dynamic ordinary least square (DOLS) estimation result demonstrated that FR has a detrimental and statistically significant impact on private investment, resulting in considerable lost opportunities for private investors by driving away banks' productive investment. In addition, the structural reforms implemented since 2011 have a beneficial and significant influence on private investment. The effects of financial development, per capita GDP, and domestic lending to the private sector all produce similar consequences. Additionally, Ethiopia's private investment is negatively impacted by trade liberalization and inflation. The primary findings are used to infer potential policy implications.